Psychotic Disorders in ICD-11 - Gaebel, W.; Zielasek, J.; Falkai, P. (Die Psychiatrie, 2015)
For the development of ICD-11, the World Health Organization (WHO) has inaugurated a Working Group on the Classification of Psychotic Disorders (WGPD). A range of changes of the classification of primary psychotic disorders was developed by this group. While DSM-5 was published in 2013, the ICD-11 proposals are currently undergoing internet-based and clinical field trials and the final version is due in 2017. Among the major changes suggested by the WGPD for ICD-11 are the chapter titles, the replacement of the current schizophrenia subtypes by a number of symptom specifiers, a new set of course specifiers harmonized with DSM-5, transsectional diagnostic criteria for schizoaffective disorder, and a reorganization of the acute and transient psychotic disorders and delusional disorders.
Keywords: Classification; mental disorders; ICD-11; DSM-5; field trials